Evaluasi dan Perbaikan Desain Antarmuka Pengguna Situs Web Indah Bordir Menggunakan Pendekatan Human Centered Design (HCD) - Achmad Fauzi; Yusi Tyroni Mursityo; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Indah Bordir is a fashion retail store that now has its own official website to expand in the world of e-commerce. But the optimization of the ecommerce website is still needed in order to expand the market reach and make it easier for consumers who are outside East Java to get products from Indah Bordir, they can order without having to visit the store. However, data from a web analysis using SEMrush.com also shows that Indah Bordir website traffic has decreased in 2019 by 77.8%. This identified a problem with the website. A solution is needed to overcome website usability issues. The study was conducted to produce an interface design that is in accordance with the rules of usability using the human centered design (HCD) approach, and also usability testing as a tool to identify existing problems related to usability levels and finally bring new needs. With so company flexibility and the number of website users is expected to increase so as to generate profits for the company. HCD is an approach to problem solving, the HCD approach is commonly used for design as well as a framework for solving problems using the full human perspective to produce solutions. This research resulted in a web site interface design solution that has been improved by using guidelines and initial evaluation results which are then re-evaluated using usability testing with different respondents, so we get a significant increase in each usability metric and user satisfaction. Based on this the Indah Bordir website design solutions are in accordance with the usability rules.